A modelling approach for the German gas grid using highly resolved spatial, temporal and sectoral data (GAMAMOD-DE) - Philipp Hauser (ZBW – Leibniz Information Centre for Economics, 2019)
Natural gas is the fossil fuel with lowest CO2-emissions, compared to coal, lignite or oil. Regarding the ongoing energy transition in Germany, the extend usage of natural gas provide advantages that might be built a bridge to a low carbon energy system until 2050. Against this backdrop, this paper introduces a model for the German natural gas market (GAMAMOD-DE) with focus on infrastructure utilisation. Following a linear optimization approach, the model considers a highly resolved grid structure of pipelines, storages and cross-border connections to neighbouring countries. The spatial and temporal resolved gas demand is divided into three different sectors: industry, heating and electricity. An application for the year 2012 shows the performance and validation of the proposed model. Results show the utilisation of infrastructure and enable an assessment of the level of security of supply during the considered time frame. In addition, the findings suggest that although European customers suffered on cold winter days in 2012, from a system part of view, the security of supply (SoS) was always ensured. Further research should focus on analysing SoS and resilience of gas networks in the mid- and long-term, especially when sector coupling between electricity and gas is far advanced.
Keywords: D61; L95; Q32; Q41; Q54; 330; Linear problem optimization; gas grid Germany; sectoral; temporal; and spatial resolved demand; energy security